A high sensitivity gas pressure sensor based on femtosecond laser micro/nano processing. Issue 197 (24th March 2019) - She, Ting; Lin, Hongfeng; Liu, Fufei; Dai, Yutang; Liu, Defeng
Abstract: A compact and novel Mach-Zehnder interferometer used for gas pressure sensing is proposed and demonstrated experimentally. The sensor is constructed by fusion splicing a short piece of dual side-hole fiber (DSHF) in between two sections of multimode fibers (MMF). Interference occurs as the optical path length difference (OPLD) between light beams along air holes and silica of the DSHF. With the opening drilled on one air hole by femtosecond laser micro/nano processing, the filled gas directly affects light beam along this air hole, which results in the interference spectrum shift. Experimental results show that the sensor exhibits a high sensitivity of −8.58 nm/MPa with the increasing gas pressure. The sensor has potential application in gas pressure sensing for its advantages of high sensitivity, low temperature crosstalk and easy fabrication.